2021
DOI: 10.1021/acsomega.0c04733
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Surface Characterization Study on the Corrosion Inhibition of Mild Steel 1030 by the Cationic Surfactant Cetrimonium Trans-4-hydroxy-cinnamate

Abstract: Effective corrosion inhibition of mild steel 1030 at 0.01 M NaCl concentration was achieved by the use of the nontoxic surfactant salt cetrimonium trans-4-hydroxy-cinnamate (CTA-4OHcinn). Polarization analysis on the steel samples immersed for 24 h in the control and CTA-4OHcinn-containing solutions shows the development of a passivation potential that is more obvious at higher inhibitor concentrations along with a maximum inhibition efficiency of 97.8%. Electrochemical impedance spectroscopy (EIS) pinpoints t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the proposed circuit, R s is the electrolyte resistance, CPE dl is the capacitance at the coating-substrate interface, R ct is the charge transfer resistance, CPE coat is the coating capacitance and R po is the coating pore resistance. In order to take into consideration surface heterogeneities, constant phase elements were employed in substitution of pure capacitances [27,28]. Table 2 shows the fitted parameters and their respective variances.…”
Section: Resultsmentioning
confidence: 99%
“…In the proposed circuit, R s is the electrolyte resistance, CPE dl is the capacitance at the coating-substrate interface, R ct is the charge transfer resistance, CPE coat is the coating capacitance and R po is the coating pore resistance. In order to take into consideration surface heterogeneities, constant phase elements were employed in substitution of pure capacitances [27,28]. Table 2 shows the fitted parameters and their respective variances.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution spectrum of Fe 2p 3/2 has peaks of Fe, FeO, and Fe 2 O 3 /FeOOH at 706.73, 710.18, and 711.88 eV. 39 The spectrum of C 1s has three peaks of CS/CO, CN, and CC/CN, at 287.78, 285.83, and 284.48 eV, respectively. 40,41 The O 1s spectrum presented peaks at 529.38, and 530.88 eV, which are assigned respectively to Fe 2 O 3 /Fe 3 O 4 and FeOOH.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…15,16 Recently, it has been reported that some organic compounds based on trans-4-hydroxy-cinnamate are nontoxic materials 17 with highly effective corrosion inhibition properties. 18,19 Herein, we reveal that by substitution of an ethoxy group on trans-4-hydroxy-cinnamate there is a significant improvement in the inhibition properties of this organic molecule. Furthermore, previous works in our group have shown that the speciation of CIs plays a critical role in identifying the correlation of the CI structure with the efficiency.…”
Section: ■ Introductionmentioning
confidence: 92%
“…20 The combination of a quaternary ammonium (CTA − ) with a designed OCI would result in possible micellar formation, as we have discussed previously. 4,19 Here, we use 24 h potentiodynamic polarization (PP) studies and electrochemical impedance spectroscopy (EIS) to determine the effect of structure and concentration on corrosion inhibition. pfg NMR diffusion measurements, molecular dynamic (MD) simulations, and Cryo-TEM are also utilized to investigate the molecular behavior and possible micelle structure with concentration and how these relate to the corrosion inhibition.…”
Section: ■ Introductionmentioning
confidence: 99%